Consumer Segmentation of Emina Cosmetics Optimal and Relevant Approach of RFM+Lifetime Analysis - Nabil Rakha Dwitya; Wirawan Istiono (SAGA: Journal of Technology and Information System, 2023)
Buyers are the most crucial entities for companies selling products, including PT Paragon Technology and Innovation. PT Paragon Technology and Innovation is a cosmetics company that oversees well-known brands such as Wardah, Emina, MakeOver, and Kahf. It is essential for this company to understand the characteristics of its buyers who purchase their products, and one way to achieve this is by conducting consumer segmentation. This consumer segmentation is carried out on customers who have purchased Emina products from March 2021 to March 2023, using three types of RFM analysis approaches: vanilla RFM analysis, RFM+Lifetime, and RFM/Lifetime, which are then grouped using the K-Means algorithm. Through the implementation of this consumer segmentation, the company can gain a deeper understanding of its buyers' behavior towards the products they offer, thereby enhancing business processes and marketing efforts. The consumer segmentation has been completed with the finding that out of the three types of RFM analysis approaches employed for consumer segmentation, the RFM+Lifetime approach is the most effective and relevant one, resulting in four categories: Make Up, Face Care, Others, and General. The Make Up category further consists of five segments, while each of the other categories contains four segments.